Virtual decoupling of mechanical systems considering the mass effect of resilient links: Theoretical and numerical studies. (15th May 2019) - Wang, Zengwei; Peng, Zhike; Liu, Chao; Shi, Xi
Highlights: The capabilities of structural dynamic decoupling are further developed. The mass effect of resilient links on the link dynamic stiffness is discussed. The estimation accuracy of decoupled transfer functions is improved. The proposed method is validated by numerical case studies. Abstract: Mechanical structures often consist of many substructures and moving parts. The dynamic characteristics of substructures are important for transfer path analysis and fault diagnosis. In this paper, the structural dynamic decoupling method is further developed by considering the mass effect of resilient links. The proposed method is able to identify decoupled transfer functions accurately, whilst eliminating the mass effect of resilient links. The mass effect of resilient links on the dynamic stiffness of the link and structural dynamic decoupling is discussed. The relationships between the decoupled transfer functions and the resilient link mass are derived in theory. The proposed method is validated by numerical case studies.